Implementasi Persetujuan Dan Pengendalian Pencemaran Lingkungan Hidup Di PT Royal Coconut Kecamatan Limboto Barat Ditinjau Dari Pasal 1338 KUH-Perdata - Mifta Huljana Usman; Nirwan Junus; Julius T. Mandjo (Lembaga Pengembangan Kinerja Dosen, 2024)
This journal discusses the influence of external and internal factors on delays in implementing environmental pollution approval and control at PT Royal Coconut. Through a case analysis approach, this research explores the impact of factors such as changes in environmental regulations, public pressure, and internal company policies on the timing of environmental approval implementation. We also consider internal organizational factors, such as risk management, corporate commitment, and technical capacity in the context of pollution control. This research explores the complex interactions between these factors and their impact on the implementation process of environmental agreements, providing in-depth insights for practitioners, policy makers and researchers interested in the field of industrial environmental management. Based on the research results, it shows that the basis for evaluating the implementation of environmental pollution control at PT Royal Coconut in West Limboto District is not in accordance with the approval, when viewed from Article 1338 of the Civil Code. The research results show non- compliance in the implementation of the agreement, which includes environmental violations and non- compliance with agreed obligations. In addition, there are several identified problems related to factors inhibiting the implementation of environmental pollution control agreements originating from internal and external factors of the company. such as, lack of legal and ethical awareness in business, lack of awareness of the impact of environmental pollution, lack of government education with the community regarding the dangers posed by factory waste, and lack of openness between the community and the management of PT Royal Coconut. So in realizing implementation it must require participation from the community and local government.